Effects of Movement Practices in Virtual Reality Environment on Range of Motion in Children With Cerebral palsy - Morteza Pourazar; Fazlolah Bagherzadeh; Davoud Houmanian (University of Tehran, 2022)
Defects such as spasm, concurrent muscle activity, muscle weakness, and range of motion affect the fine and fine motor function of children with cerebral palsy and lead to movement limitations. Despite the potential of using virtual reality in the rehabilitation of children with cerebral palsy, few studies have been conducted in this area.The purpose of the present study was to examine the effects of movement practices in virtual reality environment on range of motion in cerebral palsy children. Twenty children 7-12 years old with cerebral palsy were selected by a convenience sampling method. Participants were homogeneously placed in experimental and control groups based on the average scores. The experimental group performed bowling practice in virtual environment for 3 weeks, but the control group continued their traditional therapy program. Xbox device and universal goniometer were used as instruments. Multivariate analysis of covariance (MANCOVA) and Analyze of Covariance (ANCOVA) were used at p < 0.05 level. Based on MACNOVA test results, there was a significant difference between experimental and control groups at least in one dependent variable (shoulder, elbow, & wrist range of motion) (F = 96/43, p= 0/001). Based on the results of ANCOVA test, experimental group achieved higher averages in shoulder, elbow and wrist range of motion than control group. Virtual reality technology can be used as a treatment approach for improving upper extremity range of motion in children with hemiplegic cerebral Palsy.